Ours once more : folklore, ideology, and the making of modern Greece - Herzfeld, Michael, 1947- (Berghahn, 2020)
"When this work - one that contributes to both the history and anthropology fields - first appeared in 1982, it was hailed as a landmark study of the role of folklore in nation-building. It has since been highly influential in reshaping the analysis of Greek and European cultural dynamics. In this expanded edition, a new introduction by the author and an epilogue by Sharon Macdonald document its importance for the emergence of serious anthropological interest in European culture and society and for current debates about Greece's often contested place in the complex politics of the European Union"--